The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.4274/jcrpe.1612
|View full text |Cite
|
Sign up to set email alerts
|

Growth Patterns of Children of Same Geographic Background Reared in Different Environments

Abstract: Objective: Growth charts are essential tools used to assess children’s health status. The aim of the present study was to determine the effect of environmental factors on the growth of children of a common geographic background. We constructed growth charts for children living in the East of Turkey and compared them with those for Turkish children living in other regions or countries.Methods: Growth data were obtained from 6 917 school children living in Eastern Turkey. The median values on smoothed percentile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The Dutch population is the tallest and the Peruvian population is the shortest population in the word 46 56. Even immigrants will retain genetic potential for height, as observed in Turkish children 57. The definition of short stature emphasises that the comparison of height needs to be taken between the same population group, race, or ethnicity 58.…”
Section: Discussionmentioning
confidence: 99%
“…The Dutch population is the tallest and the Peruvian population is the shortest population in the word 46 56. Even immigrants will retain genetic potential for height, as observed in Turkish children 57. The definition of short stature emphasises that the comparison of height needs to be taken between the same population group, race, or ethnicity 58.…”
Section: Discussionmentioning
confidence: 99%
“…21 In addition, genetic influences may also influence this variable. 24 Cultural aspects can also influence the growth curve as shown in a study conducted by Bahchachi et al 25 who analyzed the growth curve of 7,772 Algerian adolescents of both sexes. The results showed that female adolescents had an average of 1.57 cm of height, whereas male adolescents had an average of 1.75 cm.…”
Section: Discussionmentioning
confidence: 99%